2019–2020 Florida Citrus Production Guide: Pesticide Application Technology - Masoud Salyani (EDIS)
This 8-page fact sheet is part of the 2019–2020 Florida Citrus Production Guide. Written by Masoud Salyani and published by the Department of Agricultural and Biological Engineering, March 2019.